Considering the Living Law as A Source in National Legal Development - Achmad Irwan Hamzani; Havis Aravik; Mukhidin Mukhidin; Eddy Praptono (Jurnal Cita Hukum, 2019)
Abstract:The construction of national law is one of the projects that has not been completed to this day in Indonesian law. Legal development should ideally pay attention to existing legal sources, especially laws that have become community culture. The results of this study show that legal development must be able to produce legal product reforms to replace the Dutch colonial legacy regulations that do not reflect the values and interests of the Indonesian people and encourage the growth of government and national development activities that originate from Pancasila and the 1945 Constitution. Incorporating the living law in the development of national law is an accommodative policy so that the national law produced is truly a product that is able to protect and protect all heterogeneous components of the Indonesian nation with their different backgrounds and legal needsKeyword: The living law, the source of law, the development of national law, Islamic law AbstrakKonstruksi hukum nasional adalah salah satu proyek yang belum selesai hingga saat ini dalam hukum Indonesia. Pengembangan hukum idealnya harus memperhatikan sumber hukum yang ada, terutama hukum yang telah menjadi budaya masyarakat. Hasil penelitian ini menunjukkan bahwa pengembangan hukum harus mampu menghasilkan reformasi produk hukum untuk menggantikan peraturan peninggalan kolonial Belanda yang tidak mencerminkan nilai-nilai dan kepentingan rakyat Indonesia dan mendorong tumbuhnya kegiatan pemerintah dan pembangunan nasional yang berasal dari Pancasila dan UUD 1945. Memasukkan hukum yang hidup dalam pengembangan hukum nasional adalah kebijakan yang akomodatif, sehingga hukum nasional yang dihasilkan benar-benar merupakan produk yang mampu melindungi semua komponen bangsa Indonesia yang heterogen dengan latar belakang dan kebutuhan hukum yang berbeda-beda.Kata Kunci: Hukum Yang Hidup, Sumber Hukum, Pengembangan Hukum Nasional, Hukum Islam AннотацияПостроение национального права является одним из проектов, который до сих пор не завершен в индонезийском законодательстве. В идеале, при развитии национального права следует обратить внимание на источники действующего права, особенно права, ставшего культурой сообщества. Результаты этого исследования показывают, что правовое развитие должно происходить в виде реформ правового продукта, чтобы заменить наследиe голландских колониальныx правил, которые не отражают ценности и интересы индонезийского народа, и стимулировать рост правительственной деятельности и национального развития, основанных на принципах Панчасилы и Конституции 1945 года. Включение действующих прав в развитие национального права является услужливой политикой, поэтому получившийся национальный закон действительно является продуктом, способным защитить все составляющие гетерогенного индонезийского народа с различным происхождением и юридическими потребностями.Ключевые Слова: Действующее Право, Правовые Источники, Развитие Национального Права, Исламское Право